An Epidemic without Enmity: Explaining the Missing Ethnic Tensions in New Haven's 1918 Influenza Epidemic - Irwin, Julia (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 2008)
Although much of the historiography of urban public health documents scapegoating of immigrant and working-class civilians during onsets of epidemic disease, the 1918 influenza epidemic in New Haven, Connecticut, suggests a very different story. A large number of industrial working-class Italians made up a significant proportion of the city's population. During the epidemic, Italians succumbed to influenza at nearly twice the rate of other residents. But, contrary to historiographic expectations, the New Haven story is one narrated by piercing silences and a distinct lack of hostility towards the immigrant community. These silences must be understood as a product of the period's political and social context. Influenza struck New Haven during the closing months of the First World War, a period marked by calls for unity, cooperation, and fierce patriotism. As Anglo citizens emphasized Americanism and assimilation, the Italian community's middle-class leadership largely acquiesced. Italian editors, physicians, business-owners, and other professionals used the epidemic period to construct a new public face of the Italian community as a modernized, patriotic, and responsible ethnic group. Simultaneously, New Haven's nationally renowned public health officials embraced a wartime vocabulary of voluntarism and civic obligation to alter civilian behaviours. They encouraged education and gentle persuasion in hygiene over more forceful coercion. Together, these community responses to influenza helped to quell potential hostilities. However, they also masked persistent inequalities in Italian health and limited the potential for real urban reforms of immigrant housing and health. Italian- and English-language publications demonstrate the diverse meanings of the influenza epidemic for different groups within the city. They also illustrate the many ways these groups used the epidemic to construct new definitions of citizenship and proper behaviour.